2017
DOI: 10.1016/j.ijom.2017.02.677
|View full text |Cite
|
Sign up to set email alerts
|

Are antithrombotic agents necessary for head and neck microvascular surgery?

Abstract: 198underwent conventional surgery based on the surgeon's experience. Condyle position and reconstructed mandible contour were evaluated based on postoperative computed tomography. Complications were also evaluated during the follow-up. Findings: Flap success rate of the patients was 95.6% (43/45). Those in the computer-assisted group presented with better outcomes of the mandibular contour (P = 0.001) and condyle position (P = 0.026). Further, they also experienced beneficial dental restoration (P = 0.011) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a previous study we have found a similar pattern in patients with normal coagulation status. 23 We believe that the signi cance of this change needs further study. We did not analyze the changes in PT because abnormal PT was seen in only three patients in this study.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study we have found a similar pattern in patients with normal coagulation status. 23 We believe that the signi cance of this change needs further study. We did not analyze the changes in PT because abnormal PT was seen in only three patients in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Different anticoagulation regimes for modification of the secondary hemostasis have been developed and are currently under investigation; further optimization of the protocols already established has been done. 54,55 Latest findings could even demonstrate the primary hemostasis being responsible for flap loss, especially in severely injured patients.…”
Section: Defect Reconstructionmentioning
confidence: 99%
“…50 Other blood vessels commonly used as receptors for the anastomosis are the superior thyroid artery and branches of the internal jugular vein whose diameters range from 1.5 to 5 mm. 51 When the blood vessels to be reconstructed have a diameter of less than 5 mm, the use of optical magnification gives us certain advantages such as:…”
Section: Optical Magnificationmentioning
confidence: 99%